Hubungan Peran Orang Tua, Penggunaan Gadget, Pertumbuhan Dan Perkembangan Dengan Perilaku Social Anak Usia 6-12 Tahun Di RT05/RW13 Pabuaran Cibinong, Bogor Tahun 2023 - Mohamad Hilal Farizqi; Adi Wijaya; Sancka Stella (Jurnal Ventilator, 2024)
Gadgets are a real form of the development of science and technology (Science and Technology) in the present and future. Of course, with the development of Science and Technology, this greatly influences human life patterns both in terms of thought patterns and behavior. Nowadays, not only adults, children can also use gadgets in everyday life and also enjoy using them, but this can lead to gadget addiction, mental, emotional and negative behavioral disorders. Research objective: to determine the relationship between the role of parents, use of gadgets, growth and development with the social behavior of children aged 6-12 years in Pabuaran Village rt05/rw13 Cibinong, Bogor, 2023. Method: The type of research used in this research is quantitative research , namely with a cross sectional approach. The population of this study was 80 respondents aged 6-12 years at Rt 05/Rw 13 Pabuaran Cibinong, Bogor. The sampling technique used total sampling with a total of 60 respondents. Data collection uses a questionnaire. Data analysis was carried out in the form of a frequency distribution and used the Chi Square test. Research results: There is a relationship between the role of parents and social behavior at Rt 05/Rw 13 Pabuaran Cibinong, Bogor in 2023, with a p-value of 0.005 with an OR value of 0.231. There is a relationship between gadget use and social behavior at Rt 05/Rw 13 Pabuaran Cibinong, Bogor in 2023, with a p-value of 0.006 with an OR value of 5.000. There is a relationship between growth and development and social behavior at Rt 05/Rw 13 Pabuaran Cibinong, Bogor in 2023, with a p-value of 0.003 with an OR value of 0.184. Conclusion: There is a relationship between the role of parents, use of gadgets, growth and development and the social behavior of children aged 6-12 years in Rt05/Rw13 pabuaran Cibinong, Bogor in 2023.